TGFβ Impairs HNF1α Functional Activity in Epithelial-to-Mesenchymal Transition Interfering With the Recruitment of CBP/p300 Acetyltransferases - Bisceglia, Francesca; Battistelli, Cecilia; Noce, Valeria; Montaldo, Claudia; Zammataro, Agatino; Strippoli, Raffaele; Tripodi, Marco; Amicone, Laura; Marchetti, Alessandra (Frontiers in Pharmacology, 2019)
The cytokine Transforming Growth Factor β (TGFβ) plays a crucial role in the induction of both epithelial-to-mesenchymal transition (EMT) program and fibro-cirrhotic process in the liver, where it contributes also to organ inflammation following several chronic injuries. All these pathological situations greatly increase the risk of hepatocellular carcinoma (HCC) and contribute to tumor progression. In particular, late-stage HCCs are characterized by constitutive activation of TGFβ pathway and by an EMT molecular signature leading to the acquisition of invasive and metastatic properties. In these pathological conditions, the cytokine has been shown to induce the transcriptional downregulation of HNF1α, a master regulator of the epithelial/hepatocyte differentiation and of the EMT reverse process, the mesenchymal-to-epithelial transition (MET). Therefore, the restoration of HNF1α expression/activity has been proposed as targeted therapeutic strategy for liver fibro-cirrhosis and late stage HCCs. In this study, TGFβ is found to trigger an early functional inactivation of HNF1α during EMT process that anticipates the effects of the transcriptional downregulation of its own gene. Mechanistically, the cytokine, while did not affect the HNF1α DNA-binding capacity, impaired its ability to recruit CBP/p300 acetyltransferases on target gene promoters and, consequently, its transactivating function. The loss of HNF1α capacity to bind to CBP/p300 and HNF1α functional inactivation have been found to correlate with a change of its PTM profile. Collectively, the results obtained in this work unveil a new level of HNF1α functional inactivation by TGFβ and contribute to shed light on the early events triggering EMT in hepatocytes. Moreover, these data suggest that the use of HNF1α as anti-EMT tool in a TGFβ-containing microenvironment may require the design of new therapeutic strategies overcoming the TGFβ-induced HNF1α inactivation.